Pemanfaatan Ampas Kopi Sebagai Media Tanam dalam Produksi Jamur Tiram Putih (Pleurotus Ostreatus) - hendry, hendry efrianto palayukan; Kembong, Renianti; Patasik, Raisak Sidang; Limbongan, Yusuf La'lang; Pata'dungan, Adewidar Marano; Tandirerung, Willy Yavet; Kannapadang, Sepsriyanti; Lempang, Pasari; Karuru, Sakti Swarno (Politeknik Negeri FakFak, 2025)
White oyster mushroom (Pleurotus ostreatus) is a type of wood fungus that can be consumed and has high nutritional content such as carbohydrates, calcium, protein, iron, fat, potassium and phosphorus. This study aims to determine the benefits of oyster mushroom growth and production (Pleurotus ostreatus) using various compositions of growing media that incorporate coffee grounds. The study was conducted from June to December 2024 at the oyster mushroom cultivation facility of the Faculty of Agriculture, Christian University of Indonesia Toraja, located in Tallunglipu District, North Toraja Regency. The research consists of three stages: the production of oyster mushroom baglogs with coffee grounds as an additional substrate, testing the effectiveness of coffee grounds as a supplementary substrate in the growing media for oyster mushrooms, and analyzing the farming business based on the production results of oyster mushrooms. The research method employed a Randomized Block Design (RBD) with five treatments: without additional coffee grounds (0%); with additional coffee grounds at 5%, 10%, 15%, and 20%. The results indicate that the treatment with 10% coffee grounds yielded the best results, with an average of 35.67 caps, a cap diameter of 9.38 cm, a stem diameter of 1.78 cm, and a mushroom weight of 391.00 grams.